2011
DOI: 10.4315/0362-028x.jfp-10-469
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Molecular Stress Response Mechanisms in Escherichia coli Contributing to Survival of Shiga Toxin-Producing Escherichia coli during Raw Milk Cheese Production

Abstract: The ability of foodborne pathogens to survive in certain foods mainly depends on stress response mechanisms. Insight into molecular properties enabling pathogenic bacteria to survive in food is valuable for improvement of the control of pathogens during food processing. Raw milk cheeses are a potential source for human infections with Shiga toxin-producing Escherichia coli (STEC). In this review, we focused on the stress response mechanisms important for allowing STEC to survive raw milk cheese production proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
10
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 215 publications
5
10
0
6
Order By: Relevance
“…In research done on humans, it has been reported that intake of yoghurt increased activity of phagocytes and natural killer cell and production of cytokine and antibody. In vitro studies on cells showed similar results, after exposure to lactic acid bacteria [28][29][30][31]. In a study by Perdigon et al [32] on mice, it was observed that feeding yoghurt and L. acidophilus and L. casei increased IgA and IgA producing cells in the animal small intestine.…”
Section: Discussionsupporting
confidence: 63%
“…In research done on humans, it has been reported that intake of yoghurt increased activity of phagocytes and natural killer cell and production of cytokine and antibody. In vitro studies on cells showed similar results, after exposure to lactic acid bacteria [28][29][30][31]. In a study by Perdigon et al [32] on mice, it was observed that feeding yoghurt and L. acidophilus and L. casei increased IgA and IgA producing cells in the animal small intestine.…”
Section: Discussionsupporting
confidence: 63%
“…Authors have observed D values of 31 min at 50°C (46), 11.51 at 55°C (47) in turkey, between 2.14 and 8.32 min at 56°C in apple juice (48), and 6.6 min at 55°C (46) and between 0.95 and 4.98 min at 58°C (49) in milk. It has also been observed that cooking temperatures of 53°C or higher result in a rapid decrease in STEC populations during the first hours of cheese making and contribute to the safety of this type of cheese (50). In our study, during ripening, these pathogens remained detectable only after enrichment.…”
Section: Discussionmentioning
confidence: 50%
“…In food products, Escherichia coli must adapt against various stressors including elevated salt concentrations and organic acids to survive. This adaptation is performed through activation of different cellular response mechanisms that may allow survival and growth in food such as raw milk cheese (Peng et al, 2011). Survival of Shiga toxin-producing E. coli (STEC) in food poses a food safety risk.…”
Section: Introductionmentioning
confidence: 99%